2007
DOI: 10.1097/mat.0b013e318158ddf6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Miniaturization of Cardiopulmonary Bypass Circuit on Blood Transfusion Requirement in Neonatal Open-Heart Surgery

Abstract: This study was undertaken to determine the impact of miniaturization of a cardiopulmonary bypass (CPB) circuit on blood transfusion and hemodynamics in neonatal open-heart surgery. Neonates (n = 102) undergoing open-heart surgery between 2002 and 2006 were included and divided into three groups: group 1 (n = 28), Dideco 902 oxygenator + 5/16" line; group 2 (n = 29), Dideco 901 oxygenator + 1/4" line; group3 (n = 45), Dideco 901 oxygenator + 3/16" arterial + 1/4" venous line. Amount of priming volume, blood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Previously, our report regarding with clinical neonatal open-heart surgery showed that decreased blood transfusion ameliorated metabolic acidosis during CPB and subsequent quick recovery in intensive care. 8 Although inflammatory markers, duration of ventilation or intensive care, and long-term neurological outcome were not evaluated in this study, we believe that elimination of blood transfusion has surely potential advantages in amelioration of inflammatory response and clinically quick recovery from surgery and hence, further investigation should be designed.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previously, our report regarding with clinical neonatal open-heart surgery showed that decreased blood transfusion ameliorated metabolic acidosis during CPB and subsequent quick recovery in intensive care. 8 Although inflammatory markers, duration of ventilation or intensive care, and long-term neurological outcome were not evaluated in this study, we believe that elimination of blood transfusion has surely potential advantages in amelioration of inflammatory response and clinically quick recovery from surgery and hence, further investigation should be designed.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3][4] To address these adverse effects of blood transfusion, various efforts have attempted in previous experimental and clinical studies. [5][6][7][8][9] Karamlou et al 5 showed that asanguineous blood priming reduced neutrophil-mediated organ dysfunction by using nonblood priming miniaturized CPB circuit in neonatal pig model. Previously, our report regarding with clinical neonatal open-heart surgery showed that decreased blood transfusion ameliorated metabolic acidosis during CPB and subsequent quick recovery in intensive care.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Using an HLM with a low priming volume and a downsized foreign material surface will reduce inflammatory reactions and foreign blood donation, most likely yielding a better outcome (10). Downsizing of individual components alone may reduce the risk of complications (11), but this downsizing has physical limits, for example, the required heat and gas exchange surfaces or the minimal operating level in the venous reservoir (4). Searching for an advanced solution, we pursued a different approach.…”
Section: Discussionmentioning
confidence: 99%